O contrato de coprodução audiovisual: uma operação econômica em rede - Salinas, Rodrigo Kopke (2016)
This work investigates the audiovisual co-production agreements in the context of a network of connected contracts. The investigation is grounded on a specific concept of contractual networks. In the legal structures of audiovisual production one may observe two distinct levels of contractual connections, one of them more intense and the other one less intense. The level of more intense connections, which corresponds to the contractual arrangements for financing, may be explained by the concept of contractual networks. In the stage of financing the paradox between competition and cooperation displays its largest intensity. We investigate whether there is a normative concept of coproduction as well as which is the anatomy of the coproduction contract. We describe the legislative history of the statutes that introduced the coproduction concept in Brazil. We consider the coproduction contract as cooperative in its nature as opposed to a bilateral arrangement. We identify the following essential elements of the coproduction contract: the separation of obligations for producing the common audiovisual work as well as the sharing of benefits and control on the coproduced work. The copyright on an audiovisual work means a share on the work’s control – the distribution rights – and a split of revenues – the sharing of economic benefits. Audiovisual production results in copyrights of a diverse range of artistic works, which entails distinct economic values with respect to the coproduced audiovisual work itself, and this dynamics has influence on the coproduction contracts. We classify the copyrights according to their economic function and importance to the co-production contracts. Tensions are conflicting situations between coproducers caused by inherent contradictions of the economic networks. We analyze tensions resulting from (i) sharing of control and benefits among co-producers of the co-produced audiovisual works; (ii) liability in case of contractual default as well as recovery of damages; (iii) statutory asymmetries of copyright protection. We examine contractual clauses whose design may either intensify or calm down tensions. In conclusion we provide recommendations for the design of contractual clauses and regulations that can mitigate, control or manage possible tensions in co-production contracts.